2015
DOI: 10.1542/peds.2014-4192
|View full text |Cite|
|
Sign up to set email alerts
|

Critical Elements in the Medical Evaluation of Suspected Child Physical Abuse

Abstract: BACKGROUND: Previous research has described variability in medical evaluation of suspected abuse. The objective of this study was to identify, through expert consensus, required and highly recommended elements of a child abuse pediatrics (CAP) evaluation for 3 common presentations of suspected physical abuse in children aged 0 to 60 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Defining needed elements and standardized documentation in the medical evaluation may provide a framework for the development of evaluation tools to make consultation notes more uniform and less subjective. Recent studies have examined different models of child abuse consultations (Keenan & Campbell, 2015), consensus processes to define key consultation elements for the medical evaluation of child abuse (Burrell et al, 2016; Campbell et al, 2015) and the use of structured information in combination with a peer review process (Lorenz et al, 2018). Recent findings suggest that structured information in cases of suspected child abuse without the social history promotes high agreement in diagnosis (Lorenz et al, 2018) while the addition or modification of social history to a CAP consultation note is capable of changing diagnosis in cases with medical uncertainty (Keenan, Cook, Olson, Bardsley, & Campbell, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining needed elements and standardized documentation in the medical evaluation may provide a framework for the development of evaluation tools to make consultation notes more uniform and less subjective. Recent studies have examined different models of child abuse consultations (Keenan & Campbell, 2015), consensus processes to define key consultation elements for the medical evaluation of child abuse (Burrell et al, 2016; Campbell et al, 2015) and the use of structured information in combination with a peer review process (Lorenz et al, 2018). Recent findings suggest that structured information in cases of suspected child abuse without the social history promotes high agreement in diagnosis (Lorenz et al, 2018) while the addition or modification of social history to a CAP consultation note is capable of changing diagnosis in cases with medical uncertainty (Keenan, Cook, Olson, Bardsley, & Campbell, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas prospective studies have identified compelling evidence for population risk indicators for child abuse, it is unknown to what extent CAP consultation notes in cases of suspected child physical abuse reflect these social risk factors. Although recent studies have used consensus processes to define key consultation elements for the medical evaluation of child abuse (Burrell, Moffatt, Toy, Nielsen-Parker, & Anderst, 2016; Campbell, Olson, & Keenan, 2015) there is still debate among CAPs regarding what elements of a child and families’ social ecology to include in the social history (Burrell et al, 2016; Campbell et al, 2015; Mian et al, 2009). The goal of this study was to qualitatively examine and describe the types of risk and protective factors recorded by CAPs as part of their comprehensive evaluation of children injured by physical abuse.…”
Section: Introductionmentioning
confidence: 99%
“…The authors used a modified Delphi method to develop consensus educational goals. The Delphi method uses an iterative process of individual survey of expert opinion, anonymous summary of responses, and group feedback of the responses, to converge on shared expert opinion . To develop the initial list of educational goals, the authors reviewed existing guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…The required elements of a CAP medical evaluation for each injury type were defined through an online Delphi process previously described (Supplemental Table 5) and served as our gold standard for comparison. 7 Complete evaluations included all elements of the gold standard. Incomplete evaluations missed 1 or more required elements.…”
Section: Medical Evaluationmentioning
confidence: 99%